The Study On Competitiveness Of E-Recruitment Practices Of SMEs In Malaysia - Ying, Piao Hui (2009)
This study is about electronic recruitment systems which improve the ability of human resource mangers to select and recruit workers more effectively in a shorter time and in a superior way that create a competitive advantage for the organization.This system is widely known as e-recruitment system.